O37 CONCOMITANT INTESTINAL RESECTION DOES NOT NEGATIVELY INFLUENCE LONG TERM OUTCOMES FOLLOWING COMPLEX ABDOMINAL WALL RECONSTRUCTION. (25th November 2021) - Layfield, David; Hagan, J.; Wright, Danette; Slade, Dominic
Abstract: Aim: Simultaneous intestinal resection increases infective risks following abdominal wall reconstruction. We investigated the frequency of those risks and its impact on long-term outcomes. Material and Methods: Analysis of prospectively accrued data from patients undergoing AWR by a single surgeon (01/01/2014–31/12/2020). Comparison between AWR with (IR-AWR) and without (AWR) concomitant intestinal resection. Clinical review was undertaken 6 monthly for 24 months with ongoing telephone follow-up thereafter. Results: 101 repairs were performed within the study period (46 AWR, 55 IR-AWR). IR-AWR patients underwent 129 gastrointestinal procedures including 30 gastrointestinal fistula, 33 small bowel, 19 colonic and 2 gastric resections. Both groups were similar in terms of smoking status, diabetes, but obesity (BMI>30) was more prevalent in AWR(23/46(50%)vs.16/55(29%); p=0.03). Hernia defects were the same for both groups; AWR median area (range) 511cm 2 (47–2171 cm 2 ) and IR+AWR 471cm 2 (50–2827cm 2 ) (p = 0.7). Post-operative wound infection was more frequent following IR-AWR (20/55(36%) (Superficial incisional=13, deep incisional=6, cavity=1) vs. 6/46(13%)(N = 5, 0, 1 respectively);Odds ratio(OR)=3.8 (95% CI1.4-10.6); p=0.01). Patients undergoing IR-AWR were also more likely to experience ileus necessitating short-term postoperative parenteral nutrition (OR 3.3(1–10.8); p=0.05) and Clavien Dindo>2 complications (OR4.4 (1.2–16.7); p=0.03). Within IR-AWR cohort there was a single anastomotic complication requiring re-laparotomy and one mesh infection treated with antibiotics. Median follow-up= 25.2 months(range 1.2–88.8). 14 patients died during follow-up (AWR 7/46(15%), IR-AWR 7/55(13%); p=0.7). 5 were lost to follow-up (3AWR, 2 IR-AWR). 12(26%) AWR and 8(15%) IR-AWR reported either persistent or delayed onset chronic abdominal wall pain post repair(P = 0.14). Recurrent hernias occurred in 7/46(15%) AWR compared with 10/55(18%)IR-AWR(p = 0.5). Conclusions: Despite more frequent short-term complications in IR-AWR patient outcomes are comparable at 2 years.